Bilayer thin films based on K3Bi2I9/MO (M=Ti, Zn, and Cu) for CO2 photoreduction (Superficies y Vacío, 2026)
This work reports the fabrication of bilayer thin films of K3Bi2I9/MO (M=Cu, Zn) as an extrinsic strategy to enhance the stability of lead-free metal halide perovskite for CO2 photoreduction. The perovskites were grown on mica substrates by the spin-coating technique, which serves as a seed layer for the deposition of TiO2, ZnO, and CuO oxides by physical (sputtering) and chemical (atomic layer deposition) techniques, respectively. The perovskite was effectively covered by simple oxides, mainly with the use of CuO by sputtering. The samples exhibited enhanced light absorption and better stability than the reference K3Bi2I9 perovskite. However, the efficiency of the bilayer films was lower than the reference for CO2 photoreduction was lower than the reference, probably due to the mismatch of the band engineering and the lower activity of the simple oxides compared to the perovskite. According to the results, the K3Bi2I9/CuO arrangement favored better stability and efficiency than the rest of the samples, which provides an alternative to design new and more stable optical devices for photocatalytic applications.